Entrepreneurship Education and Intention - Abba, Maryam Tijjani; Torsu, Abraham Lincoln; Dey, Rowland Kwami (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The paper aims to examine the effect of entrepreneurship education on entrepreneurship intention with mediating roles of entrepreneurship attitude and self-efficacy. In a style of a quantitative research, the paper applied the SPSS version 23.0 and PLS-SEM version 3.0 for the analysis to understand the cause and effect and the mean of the differences in the constructs. As a cross-sectional study, data were collected from 393 HND Students II Business School, Bauchi, Federal Polytechnic Institute, Bauchi State, Nigeria. The result of the research shows a positive and meaningful relationship between entrepreneurship education and attitudes towards entrepreneurship, entrepreneurship education and self-efficacy and self-efficacy and entrepreneurship intention. Again, a negative impact was empirically proven between entrepreneurship attitude and entrepreneurship intention and entrepreneurship education and entrepreneurship intention. However, while testing for mediating effects of entrepreneurship attitude and self-efficacy. The result reveals that entrepreneurship attitude does not mediates the link between entrepreneurship education and entrepreneurial intention, while self-efficacy links entrepreneurship education and entrepreneurial intention. The result confirms with previous studies in this field. Future studies recommends that more research should be carried out in the same institution for instance, from school of engineering, school of general studies to mention but a few. In the same vein, researchers should carry out studies from universities and colleges of education within the region. Again, entrepreneurship attitude should be used to test the moderating effect of entrepreneurship education and entrepreneurship intention and also a longitudinal study should be carried out.
Keywords: Attitude, Education; Intention; PLS-SEM; Self-efficacy